An empirical examination of the relation between debt contracts and management incentives - Begley, Joy; Feltham, Gerald A. (Journal of Accounting and Economics, 1999)
Prior research on the factors influencing the use of debt covenants restricting dividends and additional borrowing is extended by considering management incentives. When alternative incentive variables are considered separately, we find covenants have a significant, negative relation to CEO cash compensation, an insignificant relation to the value of CEO equity held, and significant positive relations to both the ratio of the value of CEO equity holdings to cash compensation and the fraction of equity held by the CEO. In two-stage simultaneous equations models, only the latter is significant when jointly considered with each of the other incentive variables.